The Characteristics of Generation Z Students and Implications for Future Learning Methods - Hendrastomo, Grendi; Januarti, Nur Endah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to uncover the characteristics of the present generation (Millennials / Gen-Z) as part of providing an overview for teachers to better understand their students, so that they have an impact on improving the quality of learning. The research used a descriptive method with a qualitative approach. The subjects of this study were students / high school students in Yogyakarta, Indonesia. Data collection techniques using observation, interviews and focus group discussions. Data analysis was carried out using an interactive approach where the data that had been collected was then reduced to simplify the information obtained and then presented and concluded descriptively. The results of this study indicate that the characteristics of today's students differ from those of the previous generation. Students currently have self-confidence, creativity, competitive competitiveness, realistic realism, curiosity, independence, and exclusive exclusivity. From the character of students, the effort to recognize the prospective teacher is to change the mindset, encourage the creativity of prospective teachers in developing the learning process and empowerment strategies, and it is necessary to develop a variety of creative and innovative learning media, able to utilize technology to support the learning process and increase the intensity of communication and encourage inclusiveness. The ability of teachers to understand the characteristics of students is the key to achieving effective and enjoyable learning. Teachers inevitably have to merge and enter into the thinking of millennials/gen-z.